2021
DOI: 10.3389/fenvs.2021.589068
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Restoration Alters Fungal Community Composition and Functional Groups in a Desert Ecosystem

Abstract: Revegetation is regarded as an effective means to improve the ecological environment in deserts and profoundly influences the potential ecological functions of the soil fungal community. Therefore, Illumina high-throughput sequencing was performed to characterize the soil fungal diversity and community composition at two soil depths (0–10 cm and 10–20 cm) with four revegetation durations (natural grassland, half-mature, nearly mature, and mature Pinus. sylvestris var. mongolica plantations) in the Mu Us Sandy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 96 publications
2
12
0
1
Order By: Relevance
“…The abundance of symbiotrophs was higher in the mixed forests than that in the pure forests. The mixed forests in our study had higher abundance of ectomycorrhizal (ECM) fungi and SOC content than other forests, which is in line with a previous finding that soil organic matter has a positive correlation with ECM fungi ( 54 , 55 ). Pathotrophic fungi are suspected of causing diseases or negatively affecting plant performance because they derive nutrient substances by attacking host cells ( 56 ).…”
Section: Discussionsupporting
confidence: 92%
“…The abundance of symbiotrophs was higher in the mixed forests than that in the pure forests. The mixed forests in our study had higher abundance of ectomycorrhizal (ECM) fungi and SOC content than other forests, which is in line with a previous finding that soil organic matter has a positive correlation with ECM fungi ( 54 , 55 ). Pathotrophic fungi are suspected of causing diseases or negatively affecting plant performance because they derive nutrient substances by attacking host cells ( 56 ).…”
Section: Discussionsupporting
confidence: 92%
“…Fungi are considered to be the main producers of soil enzymes. It was reported that the relationship between soil fungal community diversity and soil enzyme activity [ 82 , 83 ]. In our study, soil fungi with different use types and depths were correlated with different kinds of enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Inv and Alp mainly affect the fungal community in forest and Zanthoxylum planispinum soil. Studies have shown that alkaline phosphatase was mainly related to the fungal composition of grassland topsoil and mature forest subsoil [ 83 ]. Rotation and fertilization will increase the enzymes involved in organic carbon, nitrogen mineralization and decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…Water is the major limiting factor for the survival and growth of P. sylvestris due to the large water consumption for transpiration and the limitations of natural rainfall conditions in arid and semi-arid ecosystems (Hu et al, 2015;Liu et al, 2021a). In addition, soil nutrient is an essential constraining factor affecting plantation development (Zhang et al, 2021). With the development of forests, soil nutrient depletion is serious, so the nutrients used for the EcM fungal growth are limited.…”
Section: Introductionmentioning
confidence: 99%